When Teratoma Masquerades: A Rare Case of Intrapleural Mature Cystic Teratoma Mimicking Tuberculous Empyema - Nik Nuratiqah Nik Abeed; Ng Boon Hau; Nor Safiqah Sharil; Andrea Ban Yu Lin; Marfua'h Nik Ezzamudin; Hairulfaizi Haron (Respirology Case Reports)
ABSTRACT Teratomas are germ cell tumours generally gonadal in origin and very rare, arising from extra gonadal tissue. The most common extragonadal teratomas are mediastinal, and the majority are benign. We report a case of a 49‐year‐old lady with recurrent right complex pleural effusion occurring a month after the completion of treatment for tuberculous empyema. Imaging from ultrasound of the thorax and contrasted enhanced computed tomography (CECT) thorax revealed multiseptated and loculated effusion in the thorax without any mediastinal and lung involvement. Surprisingly, pleural fluids were negative for tuberculosis. Despite chest drainage and initial treatment for bacterial empyema without improvement, she underwent video assisted thoracoscopy and decortication of the right pleura, and histopathological analysis revealed a mature cystic teratoma. She was discharged in good health and under yearly surveillance. The rarity of intrapleural mature cystic teratoma and its misleading presentation due to the concurrent tuberculous empyema make this case noteworthy.